Physical fitness in professional padel: performance differences according to players’ gender and playing side position - Pradas, Francisco; Muñoz, Diego; Garcia-Gimenez, Alejandro; Moreno-Azze, Alejandro; Sánchez-Alcaraz, Bernardino J; Sánchez-Pay, Alejandro (Biology of Sport, 2025)
The aim of this study was to analyse the differences in physical fitness between professional players according to their playing position (left or right side) and gender. Thirty players, 15 men and 15 women, were distributed in two groups: players playing on the right side (men n = 7; women n = 7) and the players playing on the left side (men n = 8; women n = 8). All players were assessed using a battery of anthropometric and physical performance tests, including measurements of body composition, maximal strength, aerobic capacity, speed and agility. The results showed significant differences in parameters such as weight, height and maximum strength according to playing position in male padel. Players on the left side showed higher muscle mass and strength values (one repetition maximum) in specific exercises (squat and leg curl), while those on the right side showed better results in vertical jump tests (countermovement jump and squat jump). In female players, moderate differences were observed in VO 2max and hand grip strength (dominant and no dominant hand), with higher values in left-side players. These results highlighted specific physical demands associated with the technical-tactical functions of each playing position. These findings provide key information to design specific training programs to optimize performance according to the player’s role on the court.